2013
DOI: 10.1038/nn.3357
|View full text |Cite
|
Sign up to set email alerts
|

Degeneration and impaired regeneration of gray matter oligodendrocytes in amyotrophic lateral sclerosis

Abstract: Oligodendrocytes associate with axons to establish myelin and provide metabolic support to neurons. In the spinal cord of ALS mice, oligodendrocytes downregulate transporters that transfer glycolytic substrates to neurons and oligodendrocyte progenitors (NG2+ cells) exhibit enhanced proliferation and differentiation, although the cause of these changes in oligodendroglia is unknown. Here we report that there is extensive degeneration of gray matter oligodendrocytes in the spinal cord of ALS mice before disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

35
578
3
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 506 publications
(621 citation statements)
references
References 53 publications
35
578
3
5
Order By: Relevance
“…Finally, an involvement of ventral gray matter oligodendrocytes in pathogenesis of SOD1-linked ALS is supported by several recent studies (34)(35)(36). Both early-onset turnover of mature oligodendrocytes themselves, with activated precursor proliferation/differentiation, and toxicity conferred by dysfunctional oligodendrocytes upon motor neurons were reported.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Finally, an involvement of ventral gray matter oligodendrocytes in pathogenesis of SOD1-linked ALS is supported by several recent studies (34)(35)(36). Both early-onset turnover of mature oligodendrocytes themselves, with activated precursor proliferation/differentiation, and toxicity conferred by dysfunctional oligodendrocytes upon motor neurons were reported.…”
Section: Discussionmentioning
confidence: 57%
“…Both early-onset turnover of mature oligodendrocytes themselves, with activated precursor proliferation/differentiation, and toxicity conferred by dysfunctional oligodendrocytes upon motor neurons were reported. Reduction of SOD1 in oligodendrocytes was able to delay onset of SOD1-linked ALS in a transgenic mouse strain (34). The finding here of transfer of mutant SOD1 and putatively other cytosolic proteins to oligodendrocytes, and the potential of oligodendrocytes to transfer cytosolic proteins to motor neurons could add a further level of understanding to these observations.…”
Section: Discussionmentioning
confidence: 58%
“…patients and SOD1 G93A mice. An increase in GM3 may also potentially slow disease by promoting oligodendrocyte differentiation (6), which is adversely affected in ALS mice (37), or by inhibiting the activation of matrix metalloproteinase-9 (38), which is expressed at high levels in those MNs most vulnerable in ALS (39). Interestingly, gene expression analysis studies carried out in ALS mice have shown that HEX (an enzyme that metabolizes GM2 to GM3) mRNA level is up-regulated in MNs before and during overt signs of disease (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…1). The Mouse Cell Cycle RT 2 Profiler TM PCR Arrays containing 86 probe sets that both positively and negatively regulate the cell cycle, the transitions between each of the phases, DNA replication, checkpoints and arrest were used. Of those, only probe sets with a difference of 1.2 folds or above in expression levels, and a p-value less than 0.05 between control and CPZ groups were used for further analysis.…”
Section: Cpz Administration Upregulated the Expression Of Cell Cyclementioning
confidence: 99%
“…Malfunction of oligodendrocyte development and demyelination have been considered as a pathological substrate for cognitive dysfunction inmultiple sclerosis (MS) and schizophrenia. 1,2 Therefore, identifying and manipulating the factors regulating oligodendrocyteprecursor cells (OPCs) proliferation and differentiation are crucial to the elucidation of pathological mechanisms of demyelination diseases.…”
Section: Introductionmentioning
confidence: 99%